Gemar Qur'an "Gerakan Masyarakat Belajar Al-Qur'an" di Desa Kaloling Kabupaten Bantaeng - Santi Sarni; Jujuri Perdamaian Dunia; Nurfiah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
Community service program was conducted in Kaloling Village, Bantaeng Regency (200 km from Makassar City). Kaloling village has the characteristics of a religious community, hardworking, open-minded, and supported by educational facilities available at all levels of education. However, kaloling villagers do not have the opportunity to study the Qur'an intensively because of their daily routine and busy work. therefore, the activities of KKN STIBA Makassar in Bantaeng Regency are focused on community development programs to study the Qur'an, called "Gemar Qur'an". In its implementation, PkM began by using soar analysis approach to the needs of local community empowerment. From the analysis, the Qur'an learning movement program consists of two activities, Tahsinul Qiro'ah (improvement of qur'an reading) for Muslims and Daurah Memorization and muroja'ah Al-Qur'an for children. the result of this PkM activity is formed several learning groups of the Qur'an consisting of various age levels for tahsinul Qiro'ah activities. Other results are increased motivation and enthusiasm of children in learning, as well as playing and having fun while learning.